Introduction to this Special Issue on Ocean Acidification: The Pathway from Science to Policy - Jeremy T. Mathis; Sarah R. Cooley; Kimberly K. Yates; Phillip Williamson (Oceanography, 2015)
Ocean acidification (OA) is a progressive decrease in the pH of seawater over decades, caused primarily by uptake of excess atmospheric CO2 and accompanied by changes in seawater carbonate chemistry. Scientific studies designed to examine the effects of anthropogenic carbon dioxide (CO2) emissions on global carbon fluxes have also led to the detection of OA. During the last decade, this phenomenon has surged to the attention of not only scientists but also policymakers and the public.